LESÕES BUCAIS EM GESTANTES E SUA RELAÇÃO COM ASPECTOS BIOSSOCIAIS NO MUNICÍPIO DE FEIRA DE SANTANA - BA - Ribeiro, Marla Smille Pedrosa Cruz (2008)
During pregnancy occur in the woman organism, physiological changes as a result of high levels of sex hormones necessary to maintenance of pregnancy. Local changes also occurred during this period, including in the mouth. The objective of this study was to evaluate the relationship between lesions in the oral mucosa of pregnant who the municipality of Feira de Santana - BA and the biological and social aspects as well as the prevalence of such lesions in the sample studied. It was done a descriptive study was done where it was applied a form and an oral clinical examination was done in the sample of 204 pregnant. After the procedure of collecting data, it was done a descriptive analysis of the interest variables, and finally stratified analysis and logistic regression. The results showed that pregnant who participated in the survey had an age group that ranged from 14 to 39 years, the majority was dun, had a family income between 1 and 3 minimum wages, and reported to be housewife. 38.2% of them had some kind of lesion in mouth, and the injury that was more detected was gingivitis with 30.4% of the cases. We could conclude that pregnant who were in first 2 quarters have a lower prevalence of oral lesions than those who are in the 3 rd quarter.